2007
DOI: 10.1111/j.1399-0012.2007.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

De novo membranous nephropathy associated with donor‐specific alloantibody

Abstract: Recent evidence suggests that alloantibody may play an aetiological role in the pathogenesis of membranous glomerulopathy in native kidneys. There is an increased awareness of the significance of alloantibody on renal transplant outcome, particularly with the development of more sensitive assays. We describe a kidney transplant patient who developed de novo membranous glomerulopathy (DNMG) with heavy proteinuria in the context of a donor-specific alloantibody (DSA) directed against HLA DQ7. Proteinuria resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Honda et al reported that patients with de novo MN revealed a significantly higher frequency of histological findings associated with AMR compared to control subjects with no de novo MN (4). El Kossi et al reported a possible etiological role for DSA in the pathogenesis of de novo MN (9). Unfortunately, we could not obtain donor HLA information because the kidney was transplanted in Peru eight years previously.…”
Section: Discussionmentioning
confidence: 99%
“…Honda et al reported that patients with de novo MN revealed a significantly higher frequency of histological findings associated with AMR compared to control subjects with no de novo MN (4). El Kossi et al reported a possible etiological role for DSA in the pathogenesis of de novo MN (9). Unfortunately, we could not obtain donor HLA information because the kidney was transplanted in Peru eight years previously.…”
Section: Discussionmentioning
confidence: 99%
“…De novo development of MN after kidney transplantation in patients who did not have MN as a cause of ESRD occurs occasionally and may be associated with evidence of antibody-mediated rejection and circulating donor-specific antibodies 8082 . Whereas IgG4 is usually the dominant or co-dominant IgG subclass deposited in recurrent MN, the IgG1 subclass predominates in de novo MN 83 .…”
Section: Role Of Anti-pla2r Antibodies In Distinguishing Recurrent Frmentioning
confidence: 99%
“…De novo MN, which is the most common de novo glomerulopathy in renal allografts, affects 2–9% of renal allografts [52]. De novo MN typically occurs 24–36 months posttransplant and recurrent MN after 10–24 months [53]. The exact pathogenesis of de novo MN is not clear.…”
Section: Posttransplantation Membranous Glomerulopathymentioning
confidence: 99%